2019
DOI: 10.1002/ange.201809981
|View full text |Cite
|
Sign up to set email alerts
|

Azetidine‐Containing Alkaloids Produced by a Quorum‐Sensing Regulated Nonribosomal Peptide Synthetase Pathway in Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa displays an impressive metabolic versatility, which ensures its survival in diverse environments. Reported herein is the identification of rare azetidine‐containing alkaloids from P. aeruginosa PAO1, termed azetidomonamides, which are derived from a conserved, quorum‐sensing regulated nonribosomal peptide synthetase (NRPS) pathway. Biosynthesis of the azetidine motif has been elucidated by gene inactivation, feeding experiments, and biochemical characterization in vitro, which involves a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…The only gene in the core regulon annotated as a downstream transcriptional regulator is vqsR (PA2591). Comprising nearly half of the core regulon, the 8 RhlR-regulated genes spanning PA3326-3334 encode a recently described azetidomonamide (aze) biosynthesis regulon (PA3331 is RhlR-regulated in 4/5 isolates) [32,33]. Finally, the core regulon also includes genes coding for two hypothetical proteins (PA1221 and PA4141).…”
Section: A Core Regulon For Rhlrmentioning
confidence: 99%
“…The only gene in the core regulon annotated as a downstream transcriptional regulator is vqsR (PA2591). Comprising nearly half of the core regulon, the 8 RhlR-regulated genes spanning PA3326-3334 encode a recently described azetidomonamide (aze) biosynthesis regulon (PA3331 is RhlR-regulated in 4/5 isolates) [32,33]. Finally, the core regulon also includes genes coding for two hypothetical proteins (PA1221 and PA4141).…”
Section: A Core Regulon For Rhlrmentioning
confidence: 99%
“…Its structure is identical to azetidomonamide B that was discovered by Hong et al in parallel to our study. 11 We identified essential enzymes for azabicyclene biosynthesis by comprehensive mutational studies of the PA3326-PA3336 cluster (aze). Furthermore, we reconstituted the activity of the NRPS AzeB (PA3327) in vitro and identified a key biosynthetic intermediate produced by this enzyme.…”
mentioning
confidence: 99%
“…11 Production of 2 does not depend on azeJ, suggesting 2 does not contain the L-AZC moiety. The mass of 2 is 14 Da larger than 1, suggesting incorporation of a proline instead of L-AZC, consistent with the promiscuity of the adenylation domain of AzeB toward both L-AZC and L-Pro reported by Hong et al 11 We identified biosynthetic intermediates produced by the aze insertional mutants. The azeC mutant accumulated two metabolites displaying m/z of 221.092 (3) and 235.108 (4) (Figure 3A).…”
mentioning
confidence: 99%
“…[1][2][3] They are produced as quorum-sensing metabolites or used as self-defensing mechanisms against predation by amoebae. [4][5][6] Several Streptomyces species produced bohemamines (BHMs), featuring a pyrrolizidine core with two unprecedented methyl groups. [7][8][9][10][11][12][13][14] In contrast to plant pyrrolizidines originated from homospermidine, [15][16][17] the biosynthesis of bacterial alkaloids may involve nonribosomal peptide synthetases (NRPSs) for the formation of indolizidine intermediates, followed by consecutive reactions to generate pyrrolizidine scaffolds by Baeyer-Villiger monooxygenases (BVMOs).…”
mentioning
confidence: 99%
“…BhmK shares high sequence identity with PxaB, LgnC, AzeC, and LpiC, previously reported BMVOs involved in pyrroliziline formation (Figure S9). [3][4][5][6]14,18 We next inactivated bhmK by replacing it with a mutant copy in which bhmK was disrupted by thiostrepton-resistance gene with a kasOp* promoter (Figure S10). 29,30 The recombinants completely abolished the production of 1-3, while accumulated three new metabolites 9-10).…”
mentioning
confidence: 99%